Hollywood and whine the snippy, snotty, and scandalous things stars say about each other - Hadleigh, Boze (New York Citadel Press, 2001)
When sex kittens turn catty and star let their updos down--LOOK OUT! This lowdown collection reveals what celebrities say frankly about each other and themselves when they're wondering whether all their gain is worth the pain.

Guaranteed to amuse, these witty, gossipy, often hilarious, and sometimes poignant quotes reveal what the stars think not only about other stars but also about their off-screen selves, their problems, secrets, and their love-hate relationship with fame.

Packed with scores of celebrity photos, and nearly 2,000 morsels of backbiting, bitching, and betrayal, Hollywood and Whine could only have been compiled by an insider like author Boze Hadleigh. A fitting companion to his previous bestseller Hollywood Babble-On, this book will delight every movie fan and gossip hound.
Includes index (pages 257-264).
Keywords: Celebrities -- United States -- Quotations; Motion picture actors and actresses -- United States -- Anecdotes; Motion picture actors and actresses -- United States -- Quotations; Motion picture industry -- United States -- Anecdotes